Impacts of MSD programs: The case of InovAgro - Amare, Mulubrhan; Ghebru, Hosaena; Smart, Jenny; Zavale, Helder (International Food Policy Research Institute, 2021)
InovAgro interventions increase farmers’ use of yield-enhancing agricultural inputs. InovAgro interventions improve the number of non-InovAgro facilitated or sponsored value chain interventions. The InovAgro MSD program has more sustainable impact than non-MSD programs. The InovAgro project benefited large numbers of smallholder farmers beyond the project’s direct sphere of influence and intended beneficiaries. The combination approach of using agrodealers, lead farmers and demonstration plots appears to be necessary to achieve long-term positive effects.